Don't use CAS on this one

Algebra Level 4

n = 1 ( p = 1 ( 1 n 2 p 1 n 2 p + 1 ) ) = ? \displaystyle \sum _{ n=1 }^{ \infty }{ \left( \sum _{ p=1 }^{ \infty }{ \left( \frac { 1 }{ { n }^{ 2p } } -\frac { 1 }{ { n }^{ 2p+1 } } \right) } \right) }= \ ?


This problem is original.
1 2 \frac { 1 }{ 2 } 1 3 \frac { 1 }{ 3 } 2 1 1 4 \frac { 1 }{ 4 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pop Wong
May 18, 2020

n = 1 ( p = 1 ( 1 n 2 p 1 n 2 p + 1 ) ) \displaystyle \sum_{n=1}^\infty ( \displaystyle \sum_{p=1}^\infty ( \frac{1}{n^{2p}} - \frac{1}{n^{2p+1}} ) ) = n = 1 ( p = 1 ( n 1 n 2 p + 1 ) ) = \displaystyle \sum_{n=1}^\infty ( \displaystyle \sum_{p=1}^\infty ( \frac{n-1}{n^{2p+1}} ) ) = 0 + n = 2 ( ( n 1 ) p = 1 ( 1 n 2 p + 1 ) ) = 0 + \displaystyle \sum_{n=2}^\infty ( (n-1) \displaystyle \sum_{p=1}^\infty ( \frac{1}{n^{2p+1}} ) )

= n = 2 ( ( n 1 ) ( 1 n 3 + 1 n 5 + ) ) = \displaystyle \sum_{n=2}^\infty ( (n-1) ( \frac{1}{n^3} + \frac{1}{n^5} +\ldots ) )

= n = 2 ( n 1 n 3 ( 1 + 1 n 2 + ) ) = \displaystyle \sum_{n=2}^\infty ( \frac{n-1}{n^3} ( 1 + \frac{1}{n^2} +\ldots ) )

= n = 2 n 1 n 3 n 2 n 2 1 = \displaystyle \sum_{n=2}^\infty \frac{n-1}{n^3} \frac{n^2}{n^2-1}

= n = 2 1 n ( n + 1 ) = \displaystyle \sum_{n=2}^\infty \frac{1}{n (n+1)}

= n = 2 1 n 1 n + 1 = \displaystyle \sum_{n=2}^\infty \frac{1}{n } - \frac{1}{n+1 }

= 1 2 = \frac{1}{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...